Outcomes of Repeat Revision Anterior Cruciate Ligament Reconstruction. (June 2013) - Griffith, Timothy B.; Allen, Benjamin J.; Levy, Bruce A.; Stuart, Michael J.; Dahm, Diane L.
Background: As anterior cruciate ligament (ACL) reconstruction is performed increasingly in the United States, the rate of revision ACL reconstruction continues to rise. A paucity of literature exists with respect to repeat ACL revision surgery. Purpose: To evaluate the functional outcomes of patients who had undergone at least 2 revision ACL reconstructions. Study Design: Case series; Level of evidence, 4. Methods: The records of all patients who had undergone repeat revision ACL reconstructions between 1998 and 2009 were retrospectively reviewed. Data collected included patient demographics, operative findings, pre- and postoperative physical examination findings, radiographs, and Tegner, Lysholm, and International Knee Documentation Committee (IKDC) subjective scores. Results: Fifteen patients had undergone repeat revision ACL reconstruction during the study period. Mean age was 27 years (range, 18-57 years). Mean follow-up was 5 years (range, 2-10 years). At the time of repeat revision surgery, new tunnels were drilled in 9 of 15 (60%) cases. Of those, 8 of 9 (89%) were drilled because femoral tunnels were deemed "too anterior." During repeat revision, 11 of 15 (73%) patients were noted to have a meniscal tear, and 9 of 15 (67%) had International Cartilage Repair Society (ICRS) grade 3 or 4 chondral lesions. Mean Lysholm score was 60 preoperatively and increased to 82 postoperatively ( P < .001). Mean preoperative IKDC score was 59, which increased to 80 postoperatively ( P < .001). Mean preoperative Tegner score was 6.0. Mean postoperative Tegner score was 4.5, with only 4 of 15 (27%) patients having returned to their prior activity level ( P < .001). Two patients (13%) sustained a traumatic rerupture. Presence of grade 3 or 4 chondral lesions and body mass index greater than 28 at the time of repeat revision were associated with a "fair" or "poor" outcome by Lysholm score ( P = .007 and P = .03, respectively) and IDKC subjective scoring ( P = .04 and P = .007, respectively). Conclusion: Repeat revision ACL reconstruction may improve the functional outcomes of patients who have failed revision ACL reconstruction. Most patients do not return to prior activity level following repeat revision. Presence of grade 3 or 4 chondral lesions and body mass index greater than 28 were associated with worse outcomes.